IMPLANTACIÓN DE CONTABILIDAD COMERCIAL Y APLICACIÓN DE ANÁLISIS FINANCIERO EN EL COMERCIAL RUIZ MORA DEL CANTÓN CATAMAYO PROVINCIA DE LOJA, PERIODO 01 DE ENERO AL 30 DE ABRIL DEL 2014 - Viñan Camacho, Juliana Maritza (2016)
This thesis deals with the main objective is to IMPLEMENT COMMERCIAL APPLICATION OF ACCOUNTING AND FINANCIAL ANALYSIS IN THE COMMERCIAL RUIZ CANTON MORA CATAMAYO Loja province, PERIOD 01 JANUARY TO 30 APRIL 2014, aims to develop an accounting design whose purpose is to organize an economic and financial process that provides a quick and timely information on the economic situation - financial assistance to the owner, so get a fair idea to know, analyze and interpret all matters of the company. was implemented through the specific objectives, the first objective is to apply the accounting process in the Commercial Ruiz Mora, period January 1 to April 30, 2014, proceeded by collecting supporting documents that allowed organizing information and to give start the accounting process opening inventory to its initial position, chart of accounts, user accounts, memorandum of operations, journal, ledger, sales assistants, paid roles, and trial balance, rose in the second goal Income Statement, Statement of financial position and cash flow statement, in order to serve as instruments of financial guidance owns, that is to generate the financial statements to determine the financial situation of the business, the financial statements as performed the company, the third objective is to make financial analysis, which enables 5 the development of real, useful and timely information for sound decision-making, the implementation of vertical analysis and own financial indicators of business of the company, in order to identify and establish the economic and financial situation of the Commercial and reach valid solutions that contribute to improving the financial management of the company, the fourth objective is to develop the financial analysis report is intended to serve as a tool very useful in the decision of the owner of the company. With the results obtained after having completed thesis states that by implementing an accounting system allows the owner to know the economic and financial situation of the company, which will help make timely decisions, so that recommends to its owner take into account the accounting proposal to safeguard the resources to improve their economic solvency.